Tumor dynamics model with treatments by oncolytic virotherapy and MEK inhibitors involving TNF-α inhibitors: Stability analysis and optimal control - Daengkongkho Salinthip; Viriyapong Ratchada (Computational and Mathematical Biophysics)
Oncolytic virotherapy is one of the cancer treatments that kills cancer cells but leaves normal cells. Furthermore, mitogen-activated protein kinase (MEK) inhibitors boost chimeric antigen receptor expression and increase oncolytic virus entry into tumor cells, and TNF-α{\rm{α }} inhibitors improve the effectiveness of oncolytic virotherapy. We propose a mathematical model of tumor involving oncolytic virotherapy, MEK inhibitors, and TNF-α{\rm{α }} inhibitors. All model properties are performed. Three equilibrium points are computed, and their stabilities are analyzed. Additionally, optimal control is applied to the model to investigate the optimal strategy to reduce the load of tumor cells by using MEK inhibitors, TNF-α{\rm{α }} inhibitors, and oncolytic virotherapy. Numerical results demonstrate that a combination of all three treatments leads to a significant increase in infected tumor cells and macrophages, resulting in more infections of tumor cells and stronger immune response. Both low and high levels of MEK inhibitors are applied in three-treatment combination to explore a role of MEK inhibitors, and a better result in high level of MEK inhibitors case is obtained. Hence, our results confirm that MEK inhibitors could lead to not only more oncolytic virus infection of tumor cells and more immune of macrophages but also limit the virus replication.